Regional Governments Spending, Private Investment and Employment Performance in Indonesia - Budiyanto, Budiyanto; Priyarsono, D S; Sinaga, Bonar M; Sudaryanto, Tahlim (Badan kebijakan Fiskal, 2014)
The amount and composition of government spending in fiscal operations has a significant impact on aggregate demand and national output and affects resource allocationin an economy. Therefore, in order to achieve effective economic development, government spending has to be allocated appropriately according to the potentials of each area. Indonesia, which consists of areas with a variety of potential resources would require the determination of the amount and composition of different government spending in order to have an impact on the growth of private investment and employment opportunities are maximized. The purpose of this study is to examine the regional government expenditure performance, private investment and employment opportunities in the area where contribution of the agricultural sector to GRDP is high and low. The study utilizes an econometric model of the system of simultaneous equations using a panel of data of 20 provinces in Indonesia for the period of2003-2011. The 20 sampled provinces were classified into two groups, based on contribution of agriculture sector to the respective regional economy. The estimation results indicate that the determination of the amount of local government spending, both in the areas where the contribution of the agricultural sector to GRDP is either high or low, based on the activity or program of the previous year. Meanwhile, the greater the number of regional government spending for the agricultural sector, the private investment of agricultural sector and employment is increasing.